Alteración del color en bloques de resinas nano híbridas expuestas al humo del cigarrillo. Estudio In-Vitro. - Medina Aldaz, Diana Dayanara (2024)
The research aimed to identify color variations in blocks of nanohybrid resins exposed to cigarette smoke. The study was descriptive, cross-sectional, and experimental. The samples consisted of 30 resin blocks (G1, G2 and G3) with initial color A2, selected under inclusion and exclusion criteria; they were divided into three groups of 10 blocks each, which were exposed to cigarette smoke, where a TRIOS 3 Wireless intraoral scanner (3Shape) was used, measuring color with the VITA Classical and VITA 3D-Master models at three different times: day 0, day seven and day 14. Results showed a highly significant effect (p<0.01), indicating a substantial change in color from light to darker tones in all resins throughout the exposure period. In conclusion, after 7 days, samples G1 and G2 reach shades B4 on the VITA Classical scale, while G3 reaches B3, demonstrating a greater initial resistance to color change. However, after 14 days, all composites reach shade B4. On the VITA 3D Master scale, G1 adopts the shade (3L2.5), G2 the shade (3M3), and G3 the shade (2M3), showing less initial change. However, after 14 days, G3 presents a more pronounced change, reaching the tone (4M3). In general, all resins experience a significant color change over time.